Marriage Guardians in Indonesian and Algerian Legislation: A Comparative Analysis of the Concept of Maslahat and Gender Justice - Ghifari Hirza Firhan Ali (Legitima : Jurnal Hukum Keluarga Islam, 2024)
Purpose – The existence of guardians as a pillar of marriage has been regulated in family law in Muslim countries, two of which are Indonesia and Algeria. These two countries base each other on maslahat in formulating regulations regarding marriage guardians, but with different sociological realities and mazhab tendencies. This is due to the absence of qathi' nash that can be used as a basis for its determination. This study aims to comparatively analyze the provisions of marriage guardians in family law in Indonesia and Algeria in the concept of maslahat theory. Methods – This research uses normative juridical research methods with a statutory approach (statue approach) and comparison (comparative approach). Data sources come from secondary data sources consisting of primary legal materials in the form of Law No.1 of 1974 concerning Marriage, Compilation of Islamic Law (KHI), and Family Code 1984 (Qanun Al Usrah). Meanwhile, secondary legal materials are obtained from books and scientific articles. Findings – The results of this study indicate that the principle of the problematical provisions of marriage guardians is aimed at maintaining and safeguarding the rights of women under their guardianship. The Indonesian Marriage Law and KHI stipulate that the marriage guardian is a pillar in the marriage contract, and explains in detail the provisions relating to guardianship in marriage in line with the opinion of the majority of scholars on this matter. Meanwhile, in the Qanun Al Usrah Family Code 1984, the marriage guardian is also a pillar of the marriage contract, but it does not elaborate in detail on matters relating to guardianship in marriage. The Family Code 1984 also gives adult women the freedom to choose their guardian to be present in the marriage contract. This seems to make guardianship not one of the pillars of marriage in accordance with the Hanafiyah opinion. It appears that Algeria attempted to adopt all of the scholarly opinions in the Family Code 1984. Research implications/limitations – Looking at the modern realities in the two Muslim countries, it is appropriate to make reforms to guardianship regulations that prioritize gender equality.